Anaerobic digestion of sewage sludge pretreated by high pressure homogenization using expanded granular sludge blanket reactor: Feasibility, operation optimization and microbial community. Issue 1 (February 2021) - Nabi, Mohammad; Liang, Jinsong; Zhang, Panyue; Wu, Yan; Fu, Chuan; Wang, Siqi; Ye, Junpei; Gao, Dawen; Shah, Fayyaz Ali; Dai, Jiaqi
Graphical abstract: Highlights: Liquid-like HPH-pretreated sludge was suitable to be anaerobically digested in EGSB. Short digestion time of 5 d was needed for HPH-pretreated sludge digestion in EGSB. With the optimum conditions 240 mL/(gTCOD)·d biogas was produced. Increase in abundance of anaerobes showed successful sludge digestion in EGSB. Abstract: Biogas production via anaerobic digestion from sewage sludge have been investigated in different reactors. However, the efficient conversion of sewage sludge into biogas via continuous operational reactor with short retention time, have been overlooked. Considering the liquid-like property of sewage sludge pretreated by high pressure homogenization (HPH), in this study, the biogas production from HPH-pretreated sewage sludge was investigated in an expanded granular sludge blanket (EGSB) reactor for 219 d. Under optimized hydraulic retention time (HRT) of 6 d, upflow velocity of 4 m/h and organic loading rate (OLR) of 1.66 kg total chemical oxygen demand (TCOD)/(m 3 ·d), the raw sludge was digested with a biogas production, methane content in biogas, TCOD and volatile solid (VS) removal of 215 mL/(gTCOD)·d, 52 %, 43 % and 35 %, respectively. After sludge HPH pretreatment, the HRT was shortened to 5 d due to the sludge disintegration of 24 % and enhanced growth of acetolastic Methanosaeta and hydrogenotrophic Methanolinea, subsequently, the biogas production, methane content in biogas, TCOD and VS removal increased to 240 mL/(gTCOD)·d, 57 %, and 58 % and 43 %, respectively. Abundance of dominant bacterial phylum Chloroflexi and archaeal genera Methanosaeta significantly increased for the improvement of organic biodegradation and methane production, respectively, reflecting the successful EGSB operation. Due to the good performances of EGSB reactor for the anaerobic digestion of HPH-pretreated sewage sludge, the combined HPH-pretreatment and EGSB reactor is promising to be applied in sustainable wastewater treatment plants.